Employee Engagement: A Malaysian Insight into a Private Manufacturing Company in Negeri Sembilan - Lim, Thiam Leng (2011)
The term ‘employee engagement’ is not new in the world of management. The popularity of this concept among manufacturing organizations is mainly attributed to the implications, primarily employee loyalty and staff retention; as a result of overlooking this important area. Therefore, through a holistic approach, the purpose of this study is to identify key constructs that influence the development of employee engagement within the backdrop of manufacturing organizations in Malaysia. A quantitative survey was completed by 158 employees in one of the manufacturing companies used as the study site, in the state of Negeri Sembilan, Malaysia. The survey questionnaires included measures of five key antecedents of employee engagement identified through literature review: work passion, supervisory behavior and support, team climate, organizational commitment and age demographic. Through factor analysis that followed. Analytical procedures incorporated into this study encompassed reliability analysis, correlation analysis, multiple regression, and one-way ANOVA. Results obtained indicated that all five antecedents exhibited significant relationship in employee engagement development. However, only work passion and organizational commitments emerged as predictors of employee engagement. In addition, another vital indicator, age demographic, revealed negative relationship with employee engagement. Consequently, the proposed theoretical framework of this study was supported by hypotheses testing that verified the impact of these key antecedents towards employee engagement. Additionally, the multi-dimensional framework proposed in this study serves as a useful starting point for Human Resource departments from manufacturing companies in Negeri Sembilan to achieve a holistic employee engagement approach.